ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI GENERASI MILENIAL MUSLIM MEMILIH PERBANKAN SYARIAH - Komalasari, Salsabila Isfa; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research is aimed to analyze factors influencing muslim millennial prefrences in choosing product and service sharia banking. The independen variables in this research are advantages, knowledge, religiosity and technology. This research is descriptive qualitative research, with muslim millennial in Eest Java as the population. The data are taken directly by questionnaire from one hundred respondent. Data analysis using reliability test, validality test and classical assumption test and then multiple linear regression, T test dan F test was employed to evaluated the data. The result show that the advantage and religiosity had a significant effect on the muslim millennial preferences in choosing product and service sharia banking, while the knoweledge and Technology had no effect on on the muslim millennial preference in choosing product and service sharia banking.